Method for preparing hemostatic and anti-inflammatory chitosan-based porous nanofiber membranes and uses thereof
Patent Information
- Application Number
- CN202311727469.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-14
AI Technical Summary
[0023]1、利用5-氨基水杨酸缓释和聚多巴胺协同消炎作用,进一步促进伤口愈合速度。
Smart Images

Figure CN117982709B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane, belonging to the fields of natural polymer materials and biomedical materials. Background Technology
[0002] Chitosan is a natural product widely used in the medical field, particularly in the preparation of hemostatic materials. Its unique properties make it an excellent hemostatic agent, with applications spanning surgery, wound care, and medical emergencies. Chitosan is extracted from chitin, primarily from shrimp and crab shells. This bio-derived material is highly biocompatible and non-toxic, making it popular in medical applications. Chitosan's unique molecular structure, possessing cationic properties, is crucial for its hemostatic function. The main mechanism of chitosan in hemostasis involves its cationic properties interacting with the anionic surfaces of erythrocytes and platelets, promoting blood cell aggregation and clot formation. This clot not only fills the wound but also effectively seals blood vessels, rapidly stopping bleeding. Because chitosan can rapidly interact with blood components, it is widely used in surgery and wound care.
[0003] Compared to some synthetic hemostatic materials, chitosan exhibits excellent biocompatibility, reducing rejection reactions caused by foreign bodies. This is crucial for wound recovery and healing, helping to reduce the risk of infection and accelerate the healing process. Chitosan is absorbable, meaning it is gradually absorbed and metabolized by the body after the wound heals. This biodegradability is an important consideration in modern medicine, as it avoids the need for secondary surgery to remove the hemostatic material and reduces potential problems associated with foreign body retention. Studies have shown that chitosan also possesses certain antibacterial properties, reducing the risk of wound infection and further protecting patient health. This makes chitosan not only a hemostatic material but also a beneficial wound management tool. As a natural, biocompatible, and absorbable hemostatic material, chitosan shows broad prospects in medical applications, playing a vital role in promoting the success of surgical procedures and trauma treatment. Further improving the hemostatic performance of chitosan materials has become a research hotspot. Summary of the Invention:
[0004] To address the aforementioned technical problems, the purpose of this invention is to propose a method for preparing a hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane and its applications.
[0005] This invention is achieved through the following technical solution:
[0006] A method for preparing a hemostatic and anti-inflammatory chitosan nanofiber membrane, comprising the following steps:
[0007] Deacetylated chitosan was modified with 5-aminosalicylic acid to obtain 5-aminosalicylic acid modified chitosan.
[0008] The 5-aminosalicylic acid modified chitosan and polyvinylpyrrolidone were added to a mixed solvent of ethanol / water / acetic acid, dissolved, quenched at low temperature, then soaked in NaOH coagulation solution, washed with distilled water until neutral, and then freeze-dried to obtain a 5-aminosalicylic acid modified chitosan porous nanofiber membrane.
[0009] The 5-aminosalicylic acid modified chitosan porous nanofiber membrane is immersed in a dopamine solution, and the pH value is adjusted to 8-9, so that dopamine is deposited and polymerized on the surface of the porous fiber membrane to obtain a polydopamine-coated 5-aminosalicylic acid modified chitosan porous nanofiber membrane, namely a hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane.
[0010] As a preferred embodiment, the preparation method of the 5-aminosalicylic acid modified chitosan is as follows:
[0011] After mixing deacetylated chitosan, 5-aminosalicylic acid and 4-toluenesulfonyl chloride, triethylamine was added and stirred evenly. The mixture was then transferred to a 3% sodium bicarbonate aqueous solution, stirred, and vacuum filtered to collect the precipitate.
[0012] The precipitate was washed with deionized water and distilled water, and then with diethyl ether to obtain 5-aminosalicylic acid modified chitosan.
[0013] As a preferred embodiment, the mass ratio of the deacetylated chitosan, 5-aminosalicylic acid and 4-toluenesulfonyl chloride is (5-10):(3-6):(2-4).
[0014] As a preferred embodiment, the mass ratio of the 5-aminosalicylic acid modified chitosan to polyvinylpyrrolidone is (2-5):(1-2).
[0015] As a preferred embodiment, the quenching temperature is -30 to -10℃, the quenching time is 150 to 250℃, and the mass concentration of the NaOH solidification solution is 2 to 3%.
[0016] As a preferred embodiment, the mass concentration of the dopamine solution is 0.2% to 0.4%.
[0017] The use of a hemostatic and anti-inflammatory chitosan nanofiber membrane obtained by the aforementioned preparation method in hemostatic and anti-inflammatory materials.
[0018] The basic principle of this invention is as follows:
[0019] 1. 5-Aminosalicylic acid was grafted onto chitosan in the presence of 4-toluenesulfonyl chloride to prepare 5-aminosalicylic acid modified chitosan.
[0020] 2. A 5-aminosalicylic acid-modified chitosan / polyvinylpyrrolidone composite nanofiber membrane was prepared by thermally induced phase separation technology, and then the polyvinylpyrrolidone was removed to obtain a 5-aminosalicylic acid-modified chitosan porous nanofiber membrane.
[0021] 3. Under weakly alkaline conditions, dopamine is polymerized and loaded onto a 5-aminosalicylic acid modified chitosan porous nanofiber membrane to obtain a polydopamine-coated 5-aminosalicylic acid modified chitosan porous nanofiber membrane, namely the hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. By utilizing the sustained-release effect of 5-aminosalicylic acid and the synergistic anti-inflammatory effect of polydopamine, the wound healing speed can be further promoted.
[0024] 2. The high porosity and large specific surface area of chitosan porous nanofiber membranes can rapidly absorb plasma, causing blood cells to accumulate on the surface, thereby promoting blood coagulation on the wound surface. Attached Figure Description
[0025] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:
[0026] Figure 1 This is a roadmap for the preparation of a multifunctional chitosan-based porous nanofiber membrane dressing. Detailed Implementation
[0027] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0028] Example 1
[0029] 1 g of deacetylated chitosan, 0.5 g of 5-aminosalicylic acid, and 0.3 g of 4-toluenesulfonyl chloride were added to a three-necked flask and dissolved by magnetic stirring at room temperature. 2 g of triethylamine was then added to the mixture, and the mixture was stirred continuously for 1 hour. The resulting mixture was suspended in 250 mL of a 3% sodium bicarbonate solution and stirred for 10 hours. The precipitate was collected by vacuum filtration and thoroughly washed with deionized water and distilled water. The product was then washed with diethyl ether, and the final product was dried under vacuum at 60 °C for 24 hours to obtain 5-aminosalicylic acid-modified chitosan.
[0030] 0.5 g of 5-aminosalicylic acid-modified chitosan and 0.1 g of polyvinylpyrrolidone were added to a 15 g mixture of ethanol / water / acetic acid (mass ratio 2:10:1) and magnetically stirred until completely dissolved. The solution was then quenched in a -30°C ultra-low temperature freezer for 200 min. After quenching, a 2% NaOH solidified solution was slowly poured into the petri dish from the edge and soaked for 6 h. After soaking, the solution was rinsed with distilled water until the pH was neutral, the water was drained, and the solution was freeze-dried to obtain a 5-aminosalicylic acid-modified chitosan porous nanofiber membrane.
[0031] 0.15 g of 5-aminosalicylic acid-modified chitosan porous nanofiber membrane was immersed in 100 mL of a 0.3 mg / mL dopamine solution. The pH was adjusted to 8.5 with Tris salt buffer. After immersion for 50 min, dopamine was deposited and polymerized on the surface of the porous fibers. The membrane was then washed three times with deionized water and vacuum dried to obtain a polydopamine-coated 5-aminosalicylic acid-modified chitosan porous nanofiber membrane, i.e., a hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane. The preparation process is as follows: Figure 1 As shown.
[0032] The hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane prepared in Example 1 has a porosity of 88.3% and a specific surface area of 4.15 m². 2 / g. Using Staphylococcus aureus as the experimental subject, the colony forming units (CFU) on the culture dish were calculated to determine the bactericidal rate of the dressing, thus examining its antibacterial properties. The multifunctional composite nanofiber membrane dressing prepared in Example 1 had a bactericidal rate of 100%. The blood clotting index (BCI) was used for in vitro evaluation, and the blood clotting rate was determined by the absorbance value of the hemoglobin solution. The BCI of the hemostatic and antibacterial chitosan-based porous nanofiber membrane was 57.1%.
[0033] Example 2
[0034] 1.2 g of deacetylated chitosan, 0.6 g of 5-aminosalicylic acid, and 0.3 g of 4-toluenesulfonyl chloride were added to a three-necked flask and dissolved by magnetic stirring at room temperature. 2 g of triethylamine was added to the mixture, and the mixture was stirred continuously for 1 hour. The resulting mixture was suspended in 250 mL of a 3% sodium bicarbonate solution and stirred for 10 h. The precipitate was collected by vacuum filtration and thoroughly washed with deionized water and distilled water. The product was then washed with diethyl ether, and the final product was dried under vacuum at 60 °C for 24 h to obtain 5-aminosalicylic acid-modified chitosan.
[0035] 0.4 g of 5-aminosalicylic acid-modified chitosan and 0.2 g of polyvinylpyrrolidone were added to a mixed solvent of 15 g ethanol / water / acetic acid (mass ratio 2:10:1) and magnetically stirred until completely dissolved. The solution was then quenched in a -20°C ultra-low temperature freezer for 180 min. After quenching, a 3% NaOH solidified solution was slowly poured into the petri dish from the edge and soaked for 6 h. After soaking, the solution was rinsed with distilled water until the pH was neutral, the water was drained, and the solution was freeze-dried to obtain a 5-aminosalicylic acid-modified chitosan porous nanofiber membrane.
[0036] 0.2 g of 5-aminosalicylic acid modified chitosan porous nanofiber membrane was immersed in 100 mL of a 0.25 mg / mL dopamine solution. The pH was adjusted to 9 with Tris salt buffer, and the membrane was immersed for 30 min to allow dopamine to deposit and polymerize on the surface of the porous fibers. The membrane was then washed three times with deionized water and vacuum dried to obtain a polydopamine-coated 5-aminosalicylic acid modified chitosan porous nanofiber membrane, i.e., a hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane.
[0037] The hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane prepared in Example 2 has a porosity of 90.1% and a specific surface area of 4.44 m². 2 / g. Using Staphylococcus aureus as the experimental subject, the colony forming units (CFU) on the culture dish were calculated to determine the bactericidal rate of the dressing, thus examining its antibacterial properties. The multifunctional composite nanofiber membrane dressing prepared in Example 1 had a bactericidal rate of 100%. The blood clotting index (BCI) was used for in vitro evaluation, and the blood clotting rate was determined by the absorbance value of the hemoglobin solution. The BCI of the hemostatic and antibacterial chitosan-based porous nanofiber membrane was 58.9%.
[0038] Example 3
[0039] 1.0 g of deacetylated chitosan, 0.4 g of 5-aminosalicylic acid, and 0.2 g of 4-toluenesulfonyl chloride were added to a three-necked flask and dissolved by magnetic stirring at room temperature. 2 g of triethylamine was added to the mixture, and the mixture was stirred continuously for 1 hour. The resulting mixture was suspended in 250 mL of a 3% sodium bicarbonate solution and stirred for 10 h. The precipitate was collected by vacuum filtration and thoroughly washed with deionized water and distilled water. The product was then washed with diethyl ether, and the final product was dried under vacuum at 60 °C for 24 h to obtain 5-aminosalicylic acid-modified chitosan.
[0040] 0.4 g of 5-aminosalicylic acid-modified chitosan and 0.1 g of polyvinylpyrrolidone were added to a 15 g mixture of ethanol / water / acetic acid (mass ratio 2:10:1) and magnetically stirred until completely dissolved. The solution was then quenched in a -10°C ultra-low temperature freezer for 180 min. After quenching, a 2% NaOH solidified solution was slowly poured into the petri dish from the edge and soaked for 6 h. After soaking, the solution was rinsed with distilled water until the pH was neutral, the water was drained, and the solution was freeze-dried to obtain a 5-aminosalicylic acid-modified chitosan porous nanofiber membrane.
[0041] 0.15 g of 5-aminosalicylic acid modified chitosan porous nanofiber membrane was immersed in 100 mL of a 0.35 mg / mL dopamine solution. The pH was adjusted to 9 with Tris salt buffer. After immersion for 40 min, dopamine was deposited and polymerized on the surface of the porous fibers. Then, the fiber membrane was washed three times with deionized water and vacuum dried to obtain a polydopamine-coated 5-aminosalicylic acid modified chitosan porous nanofiber membrane, namely a hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane.
[0042] The hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane prepared in Example 3 has a porosity of 89.8% and a specific surface area of 4.12 m². 2 / g. Using Staphylococcus aureus as the experimental subject, the colony forming units (CFU) on the culture dish were calculated to determine the bactericidal rate of the dressing, thus examining its antibacterial properties. The multifunctional composite nanofiber membrane dressing prepared in Example 1 had a bactericidal rate of 100%. The blood clotting index (BCI) was used for in vitro evaluation, and the blood clotting rate was determined by the absorbance value of the hemoglobin solution. The BCI of the hemostatic and antibacterial chitosan-based porous nanofiber membrane was 56.1%.
[0043] Comparative Example 1
[0044] Unlike Example 1, Comparative Example 1 did not undergo 5-aminosalicylic acid modification; instead, chitosan was directly used in the thermally induced phase separation process to obtain a polydopamine-coated chitosan porous nanofiber membrane. The polydopamine-coated chitosan porous nanofiber membrane prepared in Comparative Example 1 had a porosity of 90.5% and a specific surface area of 4.18 m². 2 / g. The sterilization rate of the polydopamine-coated chitosan-based porous nanofiber membrane prepared in Comparative Example 1 was 72.1%. The blood clotting rate was assessed in vitro using the blood coagulation index (BCI), determined by the absorbance value of the hemoglobin solution. The BCI of the polydopamine-coated chitosan-based porous nanofiber membrane was 53.1%.
[0045] Comparative Example 2
[0046] Unlike Example 1, Comparative Example 2 did not involve polydopamine loading, ultimately yielding a 5-aminosalicylic acid-modified chitosan porous nanofiber membrane. The 5-aminosalicylic acid-modified chitosan porous nanofiber membrane prepared in Comparative Example 2 had a porosity of 91.6% and a specific surface area of 4.11 m². 2 / g. The 5-aminosalicylic acid-modified chitosan porous nanofiber membrane has a sterilization rate of 100%. The blood clotting rate was assessed in vitro using the blood coagulation index (BCI), determined by the absorbance value of the hemoglobin solution. The BCI of the 5-aminosalicylic acid-modified chitosan porous nanofiber membrane was 45.2%.
[0047] Comparative Example 3
[0048] Unlike Example 1, Comparative Example 3 did not undergo thermally induced phase separation; instead, 5-aminosalicylic acid-modified chitosan was directly used for subsequent polydopamine coating, ultimately yielding polydopamine-coated 5-aminosalicylic acid-modified chitosan. The polydopamine-coated 5-aminosalicylic acid-modified chitosan prepared in Comparative Example 3 had a porosity of 70.1% and a specific surface area of 1.11 m². 2 / g. The sterilization rate of the polydopamine-coated 5-aminosalicylic acid modified chitosan prepared in Comparative Example 3 was 100%. The blood clotting rate was assessed in vitro using the blood coagulation index (BCI), determined by the absorbance value of the hemoglobin solution. The BCI of the polydopamine-coated 5-aminosalicylic acid modified chitosan was 35.2%.
[0049] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a hemostatic and anti-inflammatory chitosan nanofiber membrane, characterized in that, Includes the following steps: Deacetylated chitosan was modified with 5-aminosalicylic acid to obtain 5-aminosalicylic acid modified chitosan. The 5-aminosalicylic acid modified chitosan and polyvinylpyrrolidone were added to a mixed solvent of ethanol / water / acetic acid, dissolved, quenched at low temperature, then soaked in NaOH coagulation solution, washed with distilled water until neutral, and then freeze-dried to obtain a 5-aminosalicylic acid modified chitosan porous nanofiber membrane. The 5-aminosalicylic acid modified chitosan porous nanofiber membrane was immersed in a dopamine solution, and the pH value was adjusted to 8-9, so that dopamine was deposited and polymerized on the surface of the porous fiber membrane to obtain a polydopamine-coated 5-aminosalicylic acid modified chitosan porous nanofiber membrane, namely a hemostatic and anti-inflammatory chitosan-based porous nanofiber membrane. The mass concentration of the dopamine solution is 0.2-0.4%.
2. The method for preparing the hemostatic and anti-inflammatory chitosan nanofiber membrane as described in claim 1, characterized in that, The preparation method of the 5-aminosalicylic acid modified chitosan is as follows: After mixing deacetylated chitosan, 5-aminosalicylic acid and 4-toluenesulfonyl chloride, triethylamine was added and stirred evenly. The mixture was then transferred to a 3% sodium bicarbonate aqueous solution, stirred, and vacuum filtered to collect the precipitate. The precipitate was washed with deionized water and distilled water, and then with diethyl ether to obtain 5-aminosalicylic acid modified chitosan.
3. The method for preparing the hemostatic and anti-inflammatory chitosan nanofiber membrane as described in claim 2, characterized in that, The mass ratio of the deacetylated chitosan, 5-aminosalicylic acid and 4-toluenesulfonyl chloride is (5~10):(3~6):(2~4).
4. The method for preparing the hemostatic and anti-inflammatory chitosan nanofiber membrane as described in claim 1, characterized in that, The mass ratio of the 5-aminosalicylic acid modified chitosan to polyvinylpyrrolidone is (2~5):(1~2).
5. The method for preparing the hemostatic and anti-inflammatory chitosan nanofiber membrane as described in claim 1, characterized in that, The quenching temperature is -30~-10℃, the quenching time is 150~250℃, and the mass concentration of the NaOH solidification solution is 2~3%.
6. The use of a hemostatic and anti-inflammatory chitosan nanofiber membrane obtained by the preparation method according to any one of claims 1 to 5 in hemostatic and anti-inflammatory materials.
Citation Information
Patent Citations
Asymmetric chitosan nanofiber porous membrane and preparation method thereof
CN103977448A
Salicylic acid and chitin-2-6-bit graft and its production
CN1982339A